Inoculation with indigenous rhizobial isolates enhanced nodulation, growth, yield and protein content of soybean (Glycine max L.) at different agro-climatic regions in Ethiopia. (2nd October 2019) - Abera, Yifru; Masso, Cargele; Assefa, Fassil
Abstract: Soybean cultivation in Ethiopia is dominated by smallholder farmers who use little or no inputs, often resulting in low yields. The use of effective rhizobia strains was considered as an ecologically and environmentally sound approach for soybean production. Field experiments were conducted during 2015/16 cropping seasons at two different agro-climatic regions in Ethiopia to investigate the effectiveness of local soybean isolates for improving nodulation, growth, yield and quality of soybean. Ten treatments comprising of seven indigenous rhizobia isolates, one exotic strain, nitrogen fertilized treatment and uninoculated control were arranged in randomized complete block design in three replications. Results of the experiment revealed that nodule number and nodule dry weight significantly increased from nil in the uninoculated control to 14–34 and 110–521 mg plant −1, respectively due to inoculation with different isolates. Furthermore, inoculation significantly increased shoot dry weight by 24–46%, shoot nitrogen concentration by 20–30%, shoot N content by 29–49%, plant height by 14–41%, pods per plant by 12–38%, seeds per pod by 7–19%, thousand seed weight by 15–24%, grain yield by 22–115% and protein content by 7–39% compared with the uninoculated control. Generally, isolates Jm-1-Bo, As-5-Aw, Bk-3-Aw, Cw-6-Aw and MAR 1495 performed better than the others in most yield parameters at both locations of which Jm-1-Bo and As-5-Aw were the local isolates performing best irrespective of location, and were superior to the effective exotic standard strain. Therefore, isolates Jm-1-Bo, As-5-Aw and Bk-3-Aw could be utilized as candidates for inoculant production at large scale in areas with similar agroecology.